1995
DOI: 10.1111/j.1365-2125.1995.tb04528.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the renin‐angiotensin and natriuretic peptide systems in the pulmonary vasculature.

Abstract: 1 The role of vasoactive peptide systems in the pulmonary vasculature has been studied much less extensively than systemic vascular and endocrine effects. The current understanding of the role of the renin-angiotensin (RAS) and natriuretic peptide systems (NPS) in the pulmonary ciruclation is therefore reviewed. 2 Plasma concentrations of angiotensin II, the main vasoactive component of the RAS, are elevated in pulmonary hypertension and may interact with hypoxaemia to cause further pulmonary vasoconstriction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 63 publications
1
18
0
1
Order By: Relevance
“…In addition to 5-HT, thromboxane, endothelin-1 and angiotensin II, which also bind to G-protein coupled receptors in the pulmonary vasculature [40], have all been reported to cause acute pulmonary arterial vasoconstriction [21,41,42]. In the present study, low doses of the thromboxane receptor agonist U46619 caused an impressive Ppa response in lungs of allergen-sensitised and -challenged mice.…”
Section: Discussionsupporting
confidence: 48%
“…In addition to 5-HT, thromboxane, endothelin-1 and angiotensin II, which also bind to G-protein coupled receptors in the pulmonary vasculature [40], have all been reported to cause acute pulmonary arterial vasoconstriction [21,41,42]. In the present study, low doses of the thromboxane receptor agonist U46619 caused an impressive Ppa response in lungs of allergen-sensitised and -challenged mice.…”
Section: Discussionsupporting
confidence: 48%
“…Activation of RAAS in PAH RAAS has long been recognised to play an important role in pulmonary vascular remodelling and pulmonary vasoconstriction [58,59]. Therefore, when captopril (the first ACE inhibitor) became commercially available, this new drug was eagerly tested in PAH patients, for whom no effective treatment existed at that time.…”
Section: Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…Since Ang II, through the AT1R receptor, is known to increase intrapulmonary blood pressure and pulmonary vascular resistance, promoting the closure of ductus arteriosus [18,19], we investigated the association between AT1R A 1166 C polymorphism and risk of PDA in 57 premature very low birth weight babies, who were born at less than 29 weeks. We found that the CC genotypecharacterized by increased Ang II-prevents PDA.…”
Section: Introductionmentioning
confidence: 99%